Remodeling of the middle third of the face with fillers - Ivy Ofenböck Magri; Mauricio de Maio (Revista Brasileira de Cirurgia Plástica)
Facial aging is a consequence of multiple intrinsic and extrinsic interactive factors, leading to loss of volume and repositioning of facial fat and bone remodeling. Breakthroughs have been seen in recent decades in the ability to reduce the signs of aging. Filling techniques and numerous products available on the market have generated new interest in the study of facial anatomy. Fillers are able to restore volume in limited areas and are suitable for treating facial wrinkles and loss of subcutaneous volume. The gold standard remains hyaluronic acid because it is more biocompatible and has greater permanence in the skin, without being definitive. The objective of this report is to review the anatomy of the middle third of the face and the main indications for filling and the techniques used for rejuvenation.